A home fitness satisfaction model for Chinese residents during the COVID-19 pandemic based on SEM analysis - Chen, Dexu; Zhang, Bin (Frontiers in Public Health, 2022)
In response to COVID-19 epidemic, General Secretary Xi Jinping proposed to take this epidemic as an opportunity to further cultivate residents’ healthy living habits and meet their demand for healthy living. Based on relevant research reviews and theoretical analysis at home and abroad, the concept model of home fitness satisfaction of Chinese residents is constructed. The research hypothesis is tested by SEM, and the conceptual model is modified. Finally, the model of home fitness satisfaction of Chinese residents is obtained. The results shows that during the epidemic period, Chinese residents' enthusiasm for home fitness remains unchanged, and online services provides powerful social support, and home fitness environment still has the enhanced space. However, some residents fails to develop regular home fitness habits. The perception of social support and home fitness environment has a positive effect on residents' home fitness harvest and satisfaction. Residents' physical literacy directly affects residents' intention for home fitness, perception of home fitness environment and social support, harvest and satisfaction of home fitness. To this end, we should use Internet, 5G, big data, cloud platform and other innovative technology means to accelerate the iterative upgrading of national fitness services, and strengthen social sports service support, multi-department cooperation, as well as the combination of online and offline to further establish and improve the home fitness service mechanism. Besides,we should reposition the important position of national fitness in building a harmonious society and comprehensively improve the residents' physical literacy.